Superior efficacy of HI-6 dimethanesulfonate over pralidoxime methylsulfate against Russian VX poisoning in cynomolgus monkeys (Macaca fascicularis) - Reymond, Chloé; Jaffré, Nina; Taudon, Nicolas; Menneteau, Mathilde; Chaussard, Hervé; Denis, Josiane; Castellarin, Cédric; Dhote, Franck; Dorandeu, Frédéric (Toxicology (Amsterdam), 2018)
Organophosphorus nerve agents still represent a serious risk to human health. In the French armed forces, the current emergency treatment against OP intoxications is a fully licensed wet-dry dual-chambered autoinjector (Ineurope ®), that contains pralidoxime methylsulfate (2-PAM) to reactivate inhibited acetylcholinesterase (AChE), atropine sulfate (AS) and avizafone chlorhydrate (AVZ). While this treatment is effective against several of the known nerve agents, it shows little efficacy against the Russian VX (VR), one of the most toxic compounds. HI-6 dimethanesulfonate (HI-6 DMS) is an oxime able to reactivate in vitro and in vivo VR-inhibited AChE. To confirm the superiority of HI-6 DMS towards 2-PAM prior to licensing, we compared the two 3-drug-combinations (HI-6 vs 2-PAM, 33 and 18 mg/kg respectively, equimolar doses; AS/AVZ 0.25/0.175 mg/kg respectively) in VR-poisoned cynomolgus macaques, the model required by the French drug regulatory agency. In parallel we performed HI-6 pharmacokinetics analysis using a one compartment model. A better efficacy of the HI-6 DMS combination was clearly observed: up to 5 LD50 of VR (i.m.), a single administration of the HI-6 DMS combination, shortly after the onset of clinical signs, prevented death of the four intoxicated animals. Conversely 2-PAM only prevented death in one out of three subjects exposed to the same amount of VR. As expected with V agents, reinhibition of blood AChE was observed but without any apparent impact on the clinical recovery of the animals. A single administration of the HI-6 DMS combination was still but partially effective at 15 LD50 of VR, allowing a 50% survival rate.